Autophagy-Related LC3 Accumulation Interacted Directly With LIR Containing RIPK1 and RIPK3, Stimulating Necroptosis in Hypoxic Cardiomyocytes - Huang, Yao; Feng, Yanhai; Cui, Lin; Yang, Lei; Zhang, Qiong; Zhang, Junhui; Jiang, Xupin; Zhang, Xingyue; Lv, Yanling; Jia, Jie-Zhi; Zhang, Dong-Xia; Huang, Yue-Sheng (Frontiers in Cell and Developmental Biology, 2021)
The exact relationships and detailed mechanisms between autophagy and necroptosis remain obscure. Here, we demonstrated the link between accumulated autophagosome and necroptosis by intervening with autophagic flux. We first confirmed that the LC3 interacting region (LIR) domain is present in the protein sequences of RIPK1 and RIPK3. Mutual effects among LC3, RIPK1 and RIPK3 have been identified in myocardium and cardiomyocytes. Direct LC3-RIPK1 and LC3-RIPK3 interactions were confirmed by pull-down assays, and their interactions were deleted after LIR domain mutation. Moreover, after disrupting autophagic flux under normoxia with bafilomycin A1 treatment, or with LC3 or ATG5 overexpression adenovirus, RIPK1, RIPK3, p-RIPK3, and p-MLKL levels increased, suggesting necroptosis activation. Severe disruptions in autophagic flux were observed under hypoxia and bafilomycin A1 co-treated cardiomyocytes and myocardium and led to more significant activation of necroptosis. Conversely, after alleviating hypoxia-induced autophagic flux impairment with LC3 or ATG5 knockdown adenovirus, the effects of hypoxia on RIPK1 and RIPK3 levels were reduced, which resulted in decreased p-RIPK3 and p-MLKL. Furthermore, necroptosis was inhibited by siRNAs against RIPK1 and RIPK3 under hypoxia or normoxia. Based on our results, LIR domain mediated LC3-RIPK1 and LC3-RIPK3 interaction. Besides, autophagosome accumulation under hypoxia lead to necrosome formation and, in turn, necroptosis, while when autophagic flux was uninterrupted, RIPK1 and RIPK3 were cleared through an autophagy-related pathway which inhibited necroptosis. These findings provide novel insights for the role of LC3 in regulating cardiomyocyte necroptosis, indicating its therapeutic potential in the prevention and treatment of hypoxic myocardial injury and other hypoxia-related diseases.